ORGANIZING COMMUNICATIVE LANGUAGE TEACHING IN GERMAN LESSONS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article discussed about Communicative Language teaching with a particular reference to the teaching and learning of German. The article deals with the educational management teaching process in Higher education. Research will explain to teachers the  method of  teaching German  as a  foreign language (GLF)  in the  classroom setting in  such a  way that  students can communicate and practice knowledge in  a  spontaneous  way,  taking  into  account  their  real experiences.  Communicative language teaching (CLT) is a language teaching method that emphasizes interaction as both the means and the goal of study. The article is illustrated clearly some examples of communicative activities which are given from the novels that can be used in a German class for non native learners of German. We can acknowledge about thoughts of great German linguistics and essential tips for learners.